Ni(II) Coordination Polymer with 3D Supramolecular Structure - Kong, Chunyan (Asian Journal of Chemistry, 2010)
One pyridinecarboxylato-bridged coordination polymers [Ni(pbc)2(H2O)2]n (Hpbc=3-pyrid-3- ylbenzoic acid) has been synthesized by the hydrothermal method and characterized by X-ray single crystal diffraction. The compound [Ni(pbc)2(H2O)2]n exhibit a 1D chain structure.